The multi-faceted role of NADPH in regulating inflammation in activated myeloid cells - Ting, Kenneth K. Y.; Jongstra-Bilen, Jenny; Cybulsky, Myron I. (Frontiers in Immunology, 2023)
Recent advances in the immunometabolism field have demonstrated the importance of metabolites in fine-tuning the inflammatory responses in myeloid cells. Cofactors, which are metabolites comprised of inorganic ions and organic molecules, may tightly or loosely bind to distinct sites of enzymes to catalyze a specific reaction. Since many enzymes that mediate inflammatory and anti-inflammatory processes require the same cofactors to function, this raises the possibility that under conditions where the abundance of these cofactors is limited, inflammatory and anti-inflammatory enzymes must compete with each other for the consumption of cofactors. Thus, this competition may reflect a naturally evolved mechanism to efficiently co-regulate inflammatory versus anti-inflammatory pathways, fine-tuning the extent of an inflammatory response. The role of NADPH, the reduced form of nicotinamide adenine dinucleotide phosphate (NADP + ), in mediating inflammatory and anti-inflammatory responses in activated myeloid cells has been well-established in the past decades. However, how the dynamic of NADPH consumption mediates the co-regulation between individual inflammatory and anti-inflammatory pathways is only beginning to be appreciated. In this review, we will summarize the established roles of NADPH in supporting inflammatory and anti-inflammatory pathways, as well as highlighting how the competition for NADPH consumption by these opposing pathways finetunes the inflammatory response in activated myeloid cells.